–463 G/A myeloperoxidase promoter polymorphism in giant cell arteritis. Issue 4 (17th August 2007) - Salvarani, C; Casali, B; Farnetti, E; Pipitone, N; Nicoli, D; Macchioni, P L; Cimino, L; Bajocchi, G L; Catanoso, M G; Pattacini, L; Ghinoi, A; Restuccia, G; et al.
Abstract : Objective: To investigate potential associations between–463 G/A myeloperoxidase (MPO) promoter polymorphism and susceptibility to, and clinical features of giant cell arteritis (GCA). Methods: A total of 156 patients with biopsy-proven GCA who were residents of Reggio Emilia, Italy, and 235 population-based controls from the same geographic area were genotyped for–463 G/A promoter polymorphism of the MPO gene by molecular methods. The patients were subgrouped according to the presence or absence of polymyalgia rheumatica and severe ischaemic complications (visual loss and/or cerebrovascular accidents). Results: The distribution of the MPO-G/A genotype differed significantly between patients with GCA and the controls (pcorr = 0.003). Allele G was significantly more frequent in patients with GCA than in the controls (pcorr = 0.0002, OR 2.0, 95% CI 1.4 to 2.9). Homozygosity for the G allele was significantly more frequent in patients with GCA than in controls (pcorr = 0.0002, OR 2.2, 95% CI 1.4 to 3.4). No significant associations were found when patients with GCA with and without polymyalgia rheumatica or with and without severe ischaemic complications were compared. Conclusions: Our findings show that the–463 G/A promoter polymorphism of the MPO gene is associated with GCA susceptibility and support a role for MPO in the pathophysiology of GCA.